An Experimental Study of the Properties of Bamboo Particle Reinforced Epoxy Matrix Biocomposites - Stephen Durowaye; Amos Abayomi; Charles Ochulor; Comfort Akindutire; Victor Okafor (Journal of Engineering)
Production of biodegradable polymer matrix biocomposites that are cost effective, sustainable, and environmentally friendly with desirable properties using particles as discontinuous phase (filler) is a welcome development. In this study, bamboo particle reinforced epoxy resin matrix biocomposites were developed by stir casting method. Varied weight percentages (5 to 30 wt. %)  of  100 µm bamboo particles were added separately and blended with an epoxy resin – hardener matrix. The blends were fed into a fabricated wooden mould and allowed to cure at room temperature. After 24 hrs, the specimens were removed from the mould and subjected to microstructural examination using a Scanning Electron Microscope (SEM). Furthermore, the physical and mechanical properties characterisation of the specimens were also carried out. The results obtained from the experiments showed the presence of pores in the microstructure of the specimens and the distribution of reinforcing particles in the epoxy matrix. The reinforced composites (S2 to S6) demonstrated an appreciable increase in density when compared with the unreinforced control specimen (C1). Specimens (S2 to S6) demonstrated lower water absorption than C1. The composites demonstrated increased ultimate tensile strength with filler addition up to 25 wt. %. Similarly, the reinforced specimens demonstrated improved hardness as the weight percent (wt. %) of bamboo particles increased up to 25 wt. %. However, the composites demonstrated a reduction in impact energy as filler content increased when compared with the control specimen. Specimen S5 formulation, which contained 25 wt. % of reinforcing particles demonstrated the best properties in terms of density, water absorption, hardness, and ultimate tensile strength. These findings highlight the effectiveness of bamboo particles in enhancing the physical and mechanical properties of the developed ecofriendly biocomposites.